Highlights From Clinical Practice Guidelines by the Infectious Diseases Society of America for the Diagnosis and Treatment of Seasonal Influenza. Issue 4 (July 2019) - File, Thomas M.
Abstract : Abstract: Seasonal influenza remains a significant cause of morbidity and mortality. The Infectious Diseases Society of America has published an update of the clinical practice guideline for the diagnosis and treatment of seasonal influenza. The guideline provides new recommendations for management of this infection. Clinicians should use rapid molecular assays for diagnosis. Antiviral therapy of patients with severe or progressive illness should be started regardless of illness duration.